PREVALÊNCIA DA DOENÇA DE CHAGAS ASSOCIADA AO MODO DE INFECÇÃO - Letícia Pâmela Garcia Ribeiro do Nascimento; Laura Maria Vidal Nogueira; Ivaneide Leal Ataíde Rodrigues; Suzana Rosa André; Victor Viana da Graça; Nicole Jucá Monteiro (Universidade Federal do Paraná, 2021)
Objective: analyze the prevalence of acute Chagas disease and association with mode of infection. Method: descriptive, quantitative study conducted in the health region of Tocantins - Pará - Brazil, with 346 cases of acute Chagas disease. The data were obtained in September 2017 and correspond to 2012-2016, from the Information system for health notification diseases. They were analyzed by Pearson's chi-square (χ²), p≤0.05, in Excel® 2013. Results: greater involvement of males (56.93%) and rural residents (56.35%). In urban areas, 110 (94%) contracted the disease orally and seven (6%) by vectorial route. In rural areas, 137 (84%) were infected orally and 26 (16%) vectorialy (p=0.010). Conclusions: the control of the disease demands specific public policies aligned to locoregional specificities. Acute Chagas disease was shown to be prevalent with an association between oral infection and urban area residents.